Circ_0000144 functions as a miR-623 sponge to enhance gastric cancer progression via up-regulating GPRC5A. Issue 8 (13th August 2020) - Mi, Lili; Lei, Lianhui; Yin, Xiaolei; Li, Ning; Shi, Jianfei; Han, Xin; Duan, Xiaoling; Zhao, Man; Han, Guangjie; Wang, Jinfeng; Yin, Fei
Abstract: Background: Gastric cancer (GC) remains one of the most common malignancies worldwide. Increasing evidence has demonstrated that circRNAs serve as critical roles in human cancer, including GC. In the present study, we focused on the detailed function and mechanism of circ_0000144 on GC progression. Methods: The levels of circ_0000144, miR-623 and G-protein-coupled receptor, family C, group 5, member A (GPRC5A) were determined by quantitative real-time polymerase chain reaction (qRT-PCR). Targeted relationships among circ_0000144, miR-623 and GPRC5A were confirmed using dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. Cell proliferation, colony formation, apoptosis, migration and invasion were evaluated by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), colony formation, flow cytometry and transwell assays. Measurement of glutamine and α-ketoglutarate (α-KG) levels was performed using a corresponding assay kit. GPRC5A protein expression was detected using Western blot. In vivo assays were used to explore the impact of circ_0000144 on tumor growth. Results: Our data indicated that circ_0000144 was up-regulated and miR-623 was down-regulated in GC tissues and cells. Circ_0000144 interacted with miR-623 through directly binding to miR-623. Moreover, the knockdown of circ_0000144 weakened GC cell proliferation, colony formation, migration, invasion and glutaminolysis and accelerated cell apoptosis by up-regulating miR-623. GPRC5A was a direct target of miR-623 and circ_0000144 protected against GPRC5A repression through sponging miR-623. Furthermore, miR-623-mediated regulation on GC cell progression was reversed by the stored expression of GPRC5A. Additionally, circ_0000144 depletion inhibited tumor growth in vivo. Conclusion: Our study indicated that circ-0000144 knockdown repressed GC progression at least partly by regulating GPRC5A expression via sponging miR-623, illumining a novel therapeutic target for GC treatment.